Diversity of Lichen in Mangrove Forest of Tomoli Village Parigi Moutong Regency - Pratama, Ari; Trianto, Manap (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2020)
Lichen is an organism resulting from a symbiotic association between fungi and algae in mutualistic symbiosis and eroticism, forming a morphological unity that is different from other species from its constituent components. This study aims to determine the level of lichen species diversity that grows in mangrove forests in Tomoli Village, Parigi Moutong Regency. This research was conducted in July 2019. The method used in this study was a survey method, the sampling technique was purposive sampling, namely by using a 10 cm x 10 cm plot on the mangrove trees in each path at the research location. The research results found ten types of lichen consisting of six genera, five families, seven orders, and four classes divided into two groups based on the kind of thallus, namely lichen crustose and foliose. The crustose lichen group is Aspicilia calcarea, Aspicilia sp, Pyrenula sp, Pyrenula dermatodes, Pyrenula santensis, Cryptothecia striata, Phaeographis sp, Graphis script, Verrucaria sp. Meanwhile, the foliose lichen group is Flavoparmelia caperata. The lichen diversity index value obtained in the mangrove forest in Tomoli Village was 2,225, indicating that the level of diversity is moderate.